Melaka Sustainability Outlook Diagnostic : Supporting Report 1 - Reinforcing Melaka’s Economic Success - Global Platform for Sustainable Cities (World Bank, Washington, DC, 2019)
Melaka State, situated roughly halfway between Kuala Lumpur and Singapore, has unique importance in the global dialogue around the sustainability of our shared urban future. At Melaka’s heart is its historic urban center, a UNESCO World Heritage Site (WHS) strategically located along the Strait of Malacca, one of the world’s busiest shipping routes and a link between the two largest countries by population, China and India. Despite Melaka State’s rapid economic growth in recent years, its future prosperity is not predetermined. Recent growth in the tourism industry has set the region on a path of extremely fast economic expansion. However, it is unclear whether this growth model has been delivering broad social benefits, and to what extent it has caused excessive stain on local infrastructure, services and historical heritage. At the same time, very ambitious development plans and largescale infrastructure investment projects have shaped government priorities, while some of the issues that persist may need further consideration in Melaka’s long-term plans. This supporting report offers a detailed analysis of recent economic development trends in Melaka City and State and compares Melaka’s performance with other similar locations in Malaysia and internationally. The report includes a strengths, weaknesses, opportunities, and threats (SWOT) analysis, along with elaborating the key message regarding Melaka’s economic competitiveness.